LVIS Jr Device for Y-Stent-Assisted Coil Embolization of Wide-Neck Intracranial Aneurysms: A Multicenter Experience - Samaniego, Edgar A. (Interv Neurol, 2018)
BACKGROUND AND PURPOSE: Complex wide-neck intracranial aneurysms are challenging to treat. We report a multicenter experience using the LVIS Jr stent for “Y-stent”-assisted coiling embolization of wide-neck bifurcation aneurysms. METHODS: Seven centers provided retrospective data on patients who underwent Y-stenting. Technical complications, immediate posttreatment angiographic results, clinical outcomes, and imaging follow-up were assessed. RESULTS: Thirty patients/aneurysms were treated: 15 basilar tip, 8 middle cerebral artery, 4 anterior communicating artery, 1 pericallosal, and 2 posterior inferior cerebellar artery aneurysms. The mean aneurysm size was 11 mm and the mean dome-to-neck ratio was 1.3 mm. Twenty-four aneurysms were unruptured and treated electively, and 6 were acutely ruptured. Fifty-eight LVIS Jr stents were successfully deployed without any technical issue. One procedural and transient in-stent thrombosis resolved with the intravenous infusion of a glycoprotein IIb/IIIa inhibitor. Five periprocedural complications (within 30 days) occurred: 2 periprocedural neurological complications (1 small temporal stroke that presented with transient aphasia and 1 posterior cerebral artery infarct) and 3 nonneurological periprocedural complications (2 retroperitoneal hematomas, and 1 patient developed a disseminated intravascular coagulopathy). One permanent complication (3.3%) directly related to Y-stenting was reported in the patient who suffered the posterior cerebral artery infarct. Immediate complete obliteration (Raymond-Roy Occlusion Classification [RROC] I–II) was achieved in 26 cases (89.6%). Twenty-four patients had clinical and imaging follow-up (mean 5.2 months). Complete angiographic occlusion (RROC I–II) was observed in 23 patients (96%). A good functional outcome with a modified Rankin Scale score ≤2 was achieved in 26 cases. CONCLUSIONS: In this multicenter case series, Y-stent-assisted coiling of wide-neck aneurysms with the LVIS Jr device was feasible and relatively safe. Follow-up imaging demonstrated very low recanalization rates.